SAP on Azure Implementation Guide: Move your business data to the cloud - Morgan, Nick; Jarkowski, Bartosz (Packt Publishing, 2020)
Learn how to migrate your SAP data to Azure simply and successfully. Key Features * Learn why Azure is suitable for business-critical systems * Understand how to migrate your SAP infrastructure to Azure * Use Lift & shift migration, Lift & migrate, Lift & migrate to HANA, or Lift & transform to S/4HANA Book Description Cloud technologies have now reached a level where even the most critical business systems can run on them. For most organizations SAP is the key business system. If SAP is unavailable for any reason then potentially your business stops. Because of this, it is understandable that you will be concerned whether such a critical system can run in the public cloud. However, the days when you truly ran your IT system on-premises have long since gone. Most organizations have been getting rid of their own data centers and increasingly moving to co-location facilities. In this context the public cloud is nothing more than an additional virtual data center connected to your existing network. There are typically two main reasons why you may consider migrating SAP to Azure: You need to replace the infrastructure that is currently running SAP, or you want to migrate SAP to a new database. Depending on your goal SAP offers different migration paths. You can decide either to migrate the current workload to Azure as-is, or to combine it with changing the database and execute both activities as a single step. SAP on Azure Implementation Guide covers the main migration options to lead you through migrating your SAP data to Azure simply and successfully. What you will learn * Successfully migrate your SAP infrastructure to Azure * Understand the security benefits of Azure * See how Azure can scale to meet the most demanding of business needs * Ensure your SAP infrastructure maintains high availability * Increase business agility through cloud capabilities * Leverage cloud-native capabilities to enhance SAP Who this book is for SAP on Azure Implementation Guide is designed to benefit existing SAP architects looking to migrate their SAP infrastructure to Azure. Whether you are an architect implementing the migration or an IT decision maker evaluating the benefits of migration, this book is for you.